Internalisasi Etos Kerja Islam dalam Upaya Meningkatkan Kinerja Pegawai Kantor Urusan Agama Siliragung - Moh.Ubay Dillah; Putri Ainur Rofiqoh; Afny Wahdiatul Hikmah; Aniqotuzzuhro' Fitriana (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2023)
This article will review the Internalization of Islamic Work Ethics in Efforts to Improve the Performance of Employees of the Office of Religious Affairs in the District of Siliragung. This study aims to find out how the internalization steps are applied to form the Islamic work ethic of employees of the Office of Religious Affairs and to find out how the application of the Islamic work ethic of employees of the Office of Religious Affairs in improving the performance of employees in the Office of Religious Affairs in Siliragung District. This type of research uses the Office of Religious Affairs descriptive research with observation, interview and documentation methods. The data obtained by the researcher is the result of an interview with the Head of the Office of Religious Affairs, Mr. Saifuddin Zuhri. The results of this study indicate that the first rare step used in the process of internalizing employees to form an Islamic work ethic is through 3 processes, including: (a). Transformation of better values by the Head of the Office of Religious Affairs to Employees. (b). Holding a training and providing motivation such as rewards to employees of the Office of Religious Affairs. (c). Implementing a better work culture and evaluating work results both from the level of the Head of the Office of Religious Affairs to the Ordinary Employee. The second result shows the application of the Islamic work ethic which has 5 systems. The impact of this internalization is a positive value that can increase morale so that it fosters the professionalism of employees of the Office of Religious Affairs at work